2009
DOI: 10.1016/j.molcel.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Scm3: A CENP-A Receptor Required for Integrity of Subkinetochore Chromatin

Abstract: SummaryThe mechanisms ensuring specific incorporation of CENP-A at centromeres are poorly understood. Mis16 and Mis18 are required for CENP-A localization at centromeres and form a complex that is conserved from fission yeast to human. Fission yeast sim1 mutants that alleviate kinetochore domain silencing are defective in Scm3Sp, the ortholog of budding yeast Scm3Sc. Scm3Sp depends on Mis16/18 for its centromere localization and like them is recruited to centromeres in late anaphase. Importantly, Scm3Sp coaffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
275
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(297 citation statements)
references
References 55 publications
(96 reference statements)
18
275
2
2
Order By: Relevance
“…23,24 Fission yeast Cnp1 and mammalian CENP-A are stably assembled into centromeres in S/G 2 phase and early G 1 , respectively, thus outside DNA replication when canonical nucleosomes are incorporated into chromatin. 20,23,25 Consistent with this, Sp Scm3 binds to centromeres in mid-late anaphase and dissociates with spindle formation in early mitosis. 20 Localization of HJURP at centromeres is also cell cycle regulated.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…23,24 Fission yeast Cnp1 and mammalian CENP-A are stably assembled into centromeres in S/G 2 phase and early G 1 , respectively, thus outside DNA replication when canonical nucleosomes are incorporated into chromatin. 20,23,25 Consistent with this, Sp Scm3 binds to centromeres in mid-late anaphase and dissociates with spindle formation in early mitosis. 20 Localization of HJURP at centromeres is also cell cycle regulated.…”
Section: Introductionsupporting
confidence: 66%
“…18,19 In S. pombe, Sp Scm3 targets Cnp1 to centromeres through binding to the proteins Mis16 and Mis18. 20,21 Bioinformatical evidences suggest that HJURP is the human homolog of Scm3. cells and finally immunoprecipitated Scm3-TAP bound to DNA with IgG dynabeads.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Mc was found to be enriched at the promoter region of scm3 (Fig. 3B), which encodes a chaperone involved in loading of the centromere-specific histone H3 variant, CENP-A (36)(37)(38). Mc likely induces the expression of this locus because a previous study has shown that scm3 is expressed at higher levels in M cells, compared with P cells (35).…”
Section: Resultsmentioning
confidence: 90%
“…The human proteins hMis18 and M18BP1, recruited to centromere at telophase-G1, and RbAp46/RbAp48 may act to prime centromere for CENP-A localization (21). In S. cerivisiae and S. pombe, Scm3 (Suppressor of chromosome mis-segregation 3) protein was shown to specifically bind the CenH3-H4 complex and to be required for its assembly into the centromeric chromatin (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%